1998
DOI: 10.1253/jcj.62.854
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Hypertrophic Cardiomyopathy With Coronary Vasospasm

Abstract: atients with hypertrophic cardiomyopathy sometimes complain of chest pain even at rest. Electrocardiogram during chest pain may show deeper ST depression than that before chest pain. Beta blockers are the most common basic treatment for hypertrophic obstructive cardiomyopathy. Although they are also commonly administered for angina pectoris on effort, they aggravate anginal attack in cases of variant angina pectoris. 1 Thus, beta-blockers must be administered carefully with nitrates and calcium antagonists in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The administration of these two drugs was effective at reducing the chest pain without causing any cardiovascular events. Comparable effects of a calcium antagonist and nitrate on coronary vasospasm in HCM patients were observed by Konishi, et al 10) They suggested that, in addition to the coronary vasodilation, an improvement of the relaxation of hypertrophied ventricle induced by calcium antagonists may be related to this chest pain ameliorating effect.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The administration of these two drugs was effective at reducing the chest pain without causing any cardiovascular events. Comparable effects of a calcium antagonist and nitrate on coronary vasospasm in HCM patients were observed by Konishi, et al 10) They suggested that, in addition to the coronary vasodilation, an improvement of the relaxation of hypertrophied ventricle induced by calcium antagonists may be related to this chest pain ameliorating effect.…”
Section: Discussionmentioning
confidence: 77%
“…3) Vasospastic angina pectoris (VSA) is usually isolated but occasionally shows a familial occurrence. [4][5][6][7][8] Whereas the coexistence of HCM and VSA has been demonstrated in some patients, [9][10] familial occurrence of both HCM and VSA has not been reported. We report here the cases of two brothers with familial HCM who are suffering from VSA concurrently.…”
mentioning
confidence: 99%
“…These reports suggested that coronary vasospasm in patients with HCM might play a potential role for the conversion of HCM to dilated cardiomyopathy, thus affecting their prognosis. Also in the clinical setting, calcium channel blockers should be the first-line therapy recommended for coronary spastic angina in HCM patients in order to induce coronary vasodilatation and to prevent the aggravation of coronary spasm by beta-blockers which are commonly administered to HCM patients to relieve chest pain [5].…”
Section: B E C Amentioning
confidence: 99%
“…Previous studies have reported that coronary vasospasm often occurs in these patients, [1][2][3] and endothelial dysfunction has been regarded as a key factor in the pathogenesis of coronary vasospasm in patients with coronary spastic angina because intracoronary injection of acetylcholine (ACh) induces coronary vasospasm. 4,5 However, ACh is not only an endothelium-dependent vasodilator, but can also serve as a potent vasoconstrictor in human coronary arteries.…”
mentioning
confidence: 99%